They wished they were honest : the Knapp Commission and New York City police corruption - Armstrong, Michael F., 1932- (Columbia University Press, 2012)
Michael Armstrong has spent close to fifty years either defending or prosecuting criminal cases in New York City. His public service has included stints as District Attorney for Queens County, New York, and chief of the Security Frauds Unit in the U.S. Attorney's office in Manhattan. None of his experiences were as tense or as dangerously waged as the Knapp Commission's investigation into police corruption, prompted by the New York Times's report on whistleblower cop Frank Serpico. Based on Armstrong's vivid recollections of this watershed moment in law enforcement accountability.